2018
DOI: 10.1038/s41438-018-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Tomato SlAN11 regulates flavonoid biosynthesis and seed dormancy by interaction with bHLH proteins but not with MYB proteins

Abstract: The flavonoid compounds are important secondary metabolites with versatile human nutritive benefits and fulfill a multitude of functions during plant growth and development. The abundance of different flavonoid compounds are finely tuned with species-specific pattern by a ternary MBW complex, which consists of a MYB, a bHLH, and a WD40 protein, but the essential role of SlAN11, which is a WD40 protein, is not fully understood in tomato until now. In this study, a tomato WD40 protein named as SlAN11 was charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 61 publications
(92 reference statements)
6
59
0
Order By: Relevance
“…It was previously reported that two bHLH TFs, SPATULA (SPT) and PHYTOCHROME INTERACTING FACTOR1 (PIF1), control seed germination and GA3OX expression in response to light and temperature signaling in Arabidopsis (Penfield et al, 2005;Oh et al, 2006). bHLH TFs also function in seed dormancy in other plant species (Gao et al, 2018;Zhao et al, 2019). These findings collectively demonstrate the conservation and diversity of the bHLH gene family in the control of dormancy.…”
Section: Nced9 Expressionmentioning
confidence: 61%
“…It was previously reported that two bHLH TFs, SPATULA (SPT) and PHYTOCHROME INTERACTING FACTOR1 (PIF1), control seed germination and GA3OX expression in response to light and temperature signaling in Arabidopsis (Penfield et al, 2005;Oh et al, 2006). bHLH TFs also function in seed dormancy in other plant species (Gao et al, 2018;Zhao et al, 2019). These findings collectively demonstrate the conservation and diversity of the bHLH gene family in the control of dormancy.…”
Section: Nced9 Expressionmentioning
confidence: 61%
“…Based on the highly conserved domains and their evolutionary relationships, this superfamily is mainly divided into 20-25 subfamilies in agronomically important plants. A wide range of extensive studies have been reported on the bHLH superfamily-related genes in plant species after genome sequences have been produced, including cucumber [5], Arabidopsis [7], apple [10], tomato [24] and Carthamus tinctorius [32]. Additionally, functional and structural characterizations of most plant bHLH proteins have been described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…The bHLH genes also regulate plant response to various abiotic stresses, such as drought [12][13][14], salinity [15][16][17], cold [18][19][20], aluminum and iron de ciency [21][22][23]. In addition, the bHLH genes play an important role in regulating multiple signal transduction pathways and impacting biosynthesis [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Among the regulatory genes, a primary role is carried out by those encoding the R2R3 MYB, the bHLH and the WD40 proteins participating in the MBW complex [ 25 , 56 ]. Most of the genes already known to be involved in the anthocyanin synthesis in tomato [ 1 , 26 , 27 ] appeared to be expressed in Aft/Aft atv/atv fruits at the time of collection and also during storage ( Fig 5 ). Only after three weeks of storage in the dark, we measured a general reduction of the mRNA level in tomato peel, attested by the low level of expression of many genes analyzed ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…SlAN1 and SlJAF13) and WD40 proteins (e.g. SlAN11) have been identified as possible candidates for the MBW complex regulating anthocyanin synthesis in tomato [ 1 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%